KAE ameliorates LPS-mediated acute lung injury by inhibiting PANoptosis through the intracellular DNA-cGAS-STING axis - Chen, Yonghu; Wu, Xilin; Jiang, Zhe; Li, Xuezheng (Frontiers in Pharmacology, 2025)
BackgroundAcute lung injury (ALI) is a severe condition characterized by inflammation, tissue damage, and persistent activation of the cyclic GMP-AMP (cGAS)-stimulator of interferon genes (STING) pathway, which exacerbates the production of pro-inflammatory mediators and promotes the progression of ALI. Specific inhibition of this pathway has been shown to alleviate ALI symptoms. Kaempferol-3-O-α-L-(4″-E-p-coumaroyl)-rhamnoside (KAE), an active compound found in the flowers of Angelica acutiloba Kitagawa, exhibits anti-inflammatory and antioxidant properties. This study aimed to investigate the molecular mechanisms through which KAE regulates the cGAS-STING pathway in the context of ALI.MethodsALI was induced using LPS. Lung damage and anti-inflammatory/antioxidant effects were assessed by H&E staining, lung edema index, and SOD, MDA, and ELISA assays. NO release and mitochondrial membrane potential (MMP) were measured by JC-1 and Griess methods. The impact of KAE on the cGAS-STING pathway and PANoptosis was analyzed using flow cytometry, Western blot, and immunofluorescence.ResultsKAE significantly alleviated lipopolysaccharide-induced pulmonary injury by reducing inflammatory cell infiltration, alleviating pulmonary edema, enhancing antioxidant capacity, and decreasing levels of inflammatory cytokines in mouse lung tissues. In both in vitro and in vivo analyses, KAE downregulated the expression of key components of the cGAS-STING pathway, including cGAS, STING, p-TBK1, and nuclear factor-κB. KAE also reduced the assembly and activation of the PANoptosome, thereby attenuating apoptosis, necroptosis, and pyroptosis. Additionally, KAE inhibited cGAS activation by restoring the MMP, which reduced the release of cytosolic DNA.ConclusionKAE improve ALI by inhibiting the release of cytosolic DNA and suppressing cGAS-STING pathway activation, thereby protecting cells from PANoptosis. Our findings provide valuable insights for the development and application of novel therapeutic strategies for ALI.